Sparisoma tuiupiranga, a new species of parrotfish (Perciformes: Labroidei: Scaridae) from Brazil, with comments on the evolution of the genus - Gasparini, João Luiz; Joyeux, Jean-Christophe; Floeter, Sergio R. (Zootaxa, 2003)
Sparisoma tuiupiranga sp. n. is described from the holotype and six paratypes obtained from two coastal islands of southeastern Brazil (20° S). The species shares with S. atomarium (Poey) a number of characteristics, including the single mid-ventral scale posterior to the insertion of the pelvic fins. It differs in respect to numerous other characters, among them heavier body proportions (body depth 42.5–47.0 %SL vs. 33.2–36.5 in S. atomarium), longer snout (13.1–14.6 %SL vs. 9.4–10.6), smaller orbit diameter (6.0–7.9 %SL vs. 8.0–10.2), higher gill raker number (17–18 vs. 12–16), darker terminal phase color (both in life and alcohol-preserved), and larger size (to 154.4mm SL vs. about 81). The known distribution extends from about 18° S to 27° S in the western Atlantic. This predominantly scraping species inhabits rocky reefs and associated macroalgae beds. The clade S. atomarium–S. tuiupiranga appears to be basal in the phylogeny of Sparisoma. The idea that one can partition scarinines and sparisomatines by historical association with different habitats (coral reefs vs. seagrass) seems too simplistic.